Inveterate traumatic dislocation of the hip: a case report - Bonaventure, E. R.; Pedrazzini, A.; Ceccarelli, F. (Acta Biomedica Atenei Parmensis, 2009)
The Authors report a case of inveterate dislocation of the left hip in a male patient of 23 years arrived at the “Centre de Reeducation Motrice” of Madagascar. The patient had an escape limping, important low back pain and limb dysmetria. He was treated with a hip arthrodesis considering the risks of infection and the economic problems of total prosthesis. We present a case of disappearance of pain and resumption of working activity.